Identification of Phenols and Triterpenoids Compounds in Michelia champaca for Treating Covid 19 Symptom by in Silico - Khoirin Maghfiroh; Sri Widyarti; Sutiman B. Sumitro (Nusantara Science and Technology Proceedings)
Michelia champaca is used by the community to treat mild diseases in the population. The plant Michelia champaca produces anti-inflammatory compounds. Some anti-inflammatory classes of compounds include Phenols and Triterpenoids. In disease prevention and treatment mechanics, COVID 19 in particular, the ability of anti-inflammatory compounds is very significant. Coronaviruses are viruses that were first described in 2019 attack the human respiratory system. Cough, a runny nose, and shortness of breath for fever are typical signs of viral infection. In defense mechanisms from coronaviruses, ACE2 is one of the inflammatory mediators used by the body. This study aimed to determine the potential of each group of Phenols and Triterpenoids compounds in Michelia champaca in binding ACE2 in Silico. The method used is docking molecule to find out the potential of anti-inflammatory compound groups. The ligands used in the study were Taraxerol, Taraxeron, Ferulic Acid, and Galic Acid. The protein used in the study was ACE2. The results showed that docking molecules for the Phenols and Triterpenoids groups separately showed that native ligand ACE2 could not bind to ligand copies of the Phenols and Triterpenoids groups. However, there are similar amino acid residues in ligand copy of Gallic acid with NAG. Gallic acid is a compound of phenols. The conclusion of this analysis is the complete ability of treatments and disease prevention in the Michelia Champaca plant as a result of COVID 19. However, the mechanism of interaction of plant compounds with proteins that play a part in the COVID 19 mechanism must still be demonstrated in vitro and in vivo in this research.